Bank Funding, Financial Instruments and Decision-Making in the Banking Industry - Carbó Valverde, Santiago; Cuadros Solas, Pedro Jesús; Rodríguez Fernández, Francisco (Palgrave Macmillan Studies in Banking and Financial Institutions, 2016)
This book provides insight into current research topics in finance and banking in the aftermath of the financial crisis. Expert authors authoritatively analyse how banks finance their activities and resolve funding issues. Chapters specifically discuss financial instruments such as corporate bonds, IPOs, sukuks and microfinance investment vehicles (MIVs) in light of the importance of institutional funding gaps. The decision-making process within the banking industry with regard to long-range financial decisions and dividend policies is also discussed.